Everywhere and all the time: accident, radical contingency, and Crash. Issue 8 (2nd August 2020) - Wylot, David
ABSTRACT: What are the politics of the accident? This essay interrogates the accident trope's dual meaning in critical theory and popular narrative as both historically endemic and conditional for a political theory of radical resistance and ethical relation. I explore this in Paul Haggis' 2004 film Crash, a popular narrative that plots the accident to provide an opening for a politics of possibility and ethical engagement. However, this essay critiques efforts to situate accidents, and therefore contingency, as both historically endemic and politically resistant, arguing for the difficulty of reading a specific theory of political and ethical decision into something ontologically given. Crash stretches contingency to incorporate temporality itself, and in doing so nullifies consideration of institutional histories of race and class, which aesthetically foregrounds and troubles related assumptions made by a critical mode that too quickly reads a specific politics and ethics into contingency's deviation from necessary law. The essay re-evaluates the accident's political and ethical coordinates through reference to Ernesto Laclau and Chantal Mouffe's theorisation of contingency as conditional for political meaning more generally. Accidents, it concludes, are politically and ethically mobile, if they, as Crash and theories of radical contingency contend, happen everywhere and all the time.